2008
DOI: 10.1007/s00467-007-0666-0
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoepithelioma-like thymic carcinoma in a 16-year-old boy with nephrotic syndrome—a case report

Abstract: Nephrotic syndrome can occur as a consequence of, among others, malignancy. In this report we describe a 16-year-old boy with secondary nephrotic syndrome associated with lymphoepithelioma-like thymic carcinoma, an extremely rare subtype ofthymic carcinoma with poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The survival time of these patients barely exceeded 1 year [5,6]. We summarize the clinical data and prognosis of the reported cases [2,3,[7][8][9][10][11][12][13][14][15][16][17][18][19] and ours ( Table 1). We can nd that the patients are dominated by adolescents and the elderly, and most patients with tumor metastasis have poor prognosis.…”
Section: Discussionmentioning
confidence: 94%
“…The survival time of these patients barely exceeded 1 year [5,6]. We summarize the clinical data and prognosis of the reported cases [2,3,[7][8][9][10][11][12][13][14][15][16][17][18][19] and ours ( Table 1). We can nd that the patients are dominated by adolescents and the elderly, and most patients with tumor metastasis have poor prognosis.…”
Section: Discussionmentioning
confidence: 94%
“…Squamous cell carcinoma and LELC are relatively common subtypes of adult thymic carcinoma. However, to the best of our knowledge, only 13 cases of LELC have been reported in children ( Table I ) ( 5 – 15 ). EBV is hypothesized to be associated with LELC and LMP-1 is considered to be a predominant EBV oncoprotein ( 7 , 24 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thymic carcinoma was previously defined as a type C thymoma by the World Health Organization ( 3 ); however, it was reclassified as a distinct entity in 2004, as it exhibits a higher cytological atypia and poorer clinical outcome compared with thymoma ( 4 ). Thymic lymphoepithelioma-like carcinoma (LELC) is a histological subtype of aggressive thymic carcinoma, which is frequently associated with the Epstein-Barr virus (EBV) and, although it is a relatively common subtype of thymic carcinoma in adults, only 13 cases have been reported in children ( 5 – 15 ). Optimal chemotherapeutic regimens have not yet been determined for the treatment of thymic carcinoma ( 16 ), thus, previous case studies were conducted based on the original regimens for advanced thymoma.…”
Section: Introductionmentioning
confidence: 99%
“…According to Bochniewska et al [39], currently children with urolithiasis account for 10% of all children hospitalized in Poland, in comparison to 2% in previous studies. In studies conducted by Kiliś-Pstrusińska et al [40], it was shown that children > 4 years of age accounted for 16% of all patients treated for urolithiasis in 1995-1999 at the Pediatric Nephrology Clinic in Wrocław. According to Gołąbek et al [41], infants and children < 2 years of age accounted for 49% of all patients with uric acid stones.…”
Section: Epidemiology Of Urolithiasismentioning
confidence: 99%